Musculoskeletal disorders (MSDs) among non-occupational motorcyclists: what are the issues? / Helmi Rashid ... [et al.] - Rashid, Helmi; Omar, Abdul Rahman; Mahmud, Zamalia; Wan Fauzi, Wan Muhammad Syahmi (Universiti Teknologi MARA, 2020)
Musculoskeletal disorders (MSDs) related to occupational work or termed as WMSDs are the most common health issues that are experienced by many workers. Either due to the human errors or inconvenient and faulty workplaces, this illness has caused both employers and employees great economic losses. However, when observing the prevalence of MSDs among motorcyclists, again the focus was put among those that use motorcycles during their duties making it very much work-related. For example, police riders, postal delivery workers, and currently food delivery services. But how about those non-occupational motorcyclists or commuting workers or students that only use their motorcycle to commute to work, riding to class or weekend-motorcyclists going for prolonged motorcycle rides? Upon this matter, it became the motivation of this study to look into the possibilities of MSDs prevalence especially related to muscle fatigue among these groups of motorcyclists based on a survey and indoor prolonged motorcycle riding simulations that were conducted earlier. This includes how education and proper training could help them to reduce the risk of experiencing MSDs. Outcomes of this study suggested several other MSD issues that are possible to take place involving other body regions and establishing a prolonged riding guideline could educate them to be more aware of this issue. These possible MSDs were found to not being highlighted in work-related MSDs literature with respect to motorcyclists and very few detailed guidelines are available to educate motorcyclists for a much safer prolonged riding which provide gaps for further investigation and validation.